Percutaneous transluminal septal myocardial ablation (PTSMA) of hypertrophic cardiomyopathy: Indonesian initial experience (Medical Journal of Indonesia, 2010)
Aim Percutaneous transluminal septal myocardial ablation (PTSMA), a non-surgical intervention to treat hypertrophic cardiomyopathy (HCM), has been a standard treatment in developed countries. However, this procedure not yet systematically performed in Indonesia. This case series aim to study feasibility, safety and efficacy of PTSMA in National Cardiovascular Center Harapan Kita, Jakarta. Methods Three HCM patients (2 male) with dynamic left ventricle outflow tract (LVOT) pressure gradient of higher than 30 mmHg underwent PTSMA. Left ventricle apex pressure was measured using multipurpose catheter and aortic pressure was measured by means of left coronary guiding catheter simultaneously. Target vessel is confirmed by myocardial echocardiography contrast. Two ml absolute alcohol delivered to the target vessel by means over the wire balloon. Immediate pressure gradient changed 10 minute after alcohol administration was recorded. Continuous ECG monitoring is attemted along the procedure. Results All subject demonstrated more than 50% LVOT pressure gradient reduction. One subject experienced transient total AV block and right bundle branch block which completely recovered 6 hours after procedure. In one patient, target vessel must be changed as it gives perfusion to extensive area of right ventricle. Conclusion PTSMA guided with myocardial echocardiography contrast is feasible, safe and effective to reduce LVOT pressure gradient in HCM patient. (Med J Indones 2009;19:164-71)